2018
DOI: 10.5507/bp.2017.057
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome - from etiopathogenesis to therapy

Abstract: Irritable bowel syndrome (IBS) is a chronic and relapsing functional gastrointestinal disorder that affects 9-23% of the population across the world. Patients with IBS are often referred to gastroenterology, undergo various investigations, take various medicines, take time off work and have a poor quality of life. The pathophysiology of IBS is not yet completely understood and seems to be multifactorial. Many pathogenetic factors, in various combinations, and not all necessarily present in each patient, can pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 87 publications
0
35
0
3
Order By: Relevance
“…A significant correlation has been demonstrated between serotonin polymorphisms and chronic visceral pain severity. For example, in patients with irritable bowel syndrome, it was observed that plasma serotonin concentrations were reduced in patients with constipation but elevated in those with diarrhea [52]. Therefore, there has been considerable interest in these receptors as possible therapeutic targets [52].…”
Section: Mechanism Of Painmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant correlation has been demonstrated between serotonin polymorphisms and chronic visceral pain severity. For example, in patients with irritable bowel syndrome, it was observed that plasma serotonin concentrations were reduced in patients with constipation but elevated in those with diarrhea [52]. Therefore, there has been considerable interest in these receptors as possible therapeutic targets [52].…”
Section: Mechanism Of Painmentioning
confidence: 99%
“…For example, in patients with irritable bowel syndrome, it was observed that plasma serotonin concentrations were reduced in patients with constipation but elevated in those with diarrhea [52]. Therefore, there has been considerable interest in these receptors as possible therapeutic targets [52]. A possible role of genetic polymorphisms coding for anti-inflammatory and proinflammatory interleukins (IL), a-2 adrenergic receptors, and serotonin and cholecystokinin (CCK) receptors has also been suggested [52].…”
Section: Mechanism Of Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Many patients suffering from IBS choose to be treated with traditional Chinese medicine or integrated therapies with decreased side effects instead of taking conventional medications . However, the treatment for IBS with elusive pathophysiology is far from multidisciplinary . Therefore, it is urgent to find molecular mechanism underlying IBS for more treatment options.…”
Section: Introductionmentioning
confidence: 99%